Pelatihan Budidaya Jamur Tiram Putih (Pleurotus ostreatus) di Pondok Pesantren Hidayaturrahman NW Manggala - Hunaepi Hunaepi; Taufik Samsuri; Muhammad Asy'ari; Baiq Mirawati; Laras Firdaus; Herdiyana Fitriani; Agus Muliadi; Muhali Muhali; Saiful Prayogi (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2019)
Hidayaturrahman Islamic Boarding School NW Manggala organizes formal education at the junior high and high school levels. After graduating as santri who continue to tertiary education and some who quit education and work to help parents. Therefore, the provision of skills is needed capital to be independent. The provision of learning skills obtained at school is completed at a minimum because the teacher (teacher) does not have an entrepreneurial background. This dedication is done with the aim that the students have the ability in the cultivation of oyster mushrooms. The method used in this activity is the diffusion method of science and technology. With work procedures, namely 1) planning, 2) action, 3) mentoring, 4) evaluation. The result of this activity is that this service activity is able to improve the skills of students in the cultivation of oyster mushrooms, increase the interest and motivation of students in terms of entrepreneurship.